CDAU promotional campaign. - Chew, Pamela Siew Kim. (2008)
Having started fairly recently in April 2006, not many people have heard of the Civil Defence Auxiliary Unit (CDAU), the uniformed voluntary arm of the Singapore Civil Defence Force (SCDF). Increasing the target audience’s awareness of the auxiliary unit, their interest and their desire to volunteer with the unit are the main objectives of the team’s campaign, while attracting more suitable volunteers is a secondary objective. The core of the campaign is a series of roadshows held at various public hospitals over a three-week period and a CDAU open house event held at the Alexandra Fire Station. The approach is a fresh one as previous promotional efforts had not targeted medical personnel.